KINERJA PEGAWAI DILIHAT DARI KOMUNIKASI ORGANISASI DAN LINGKUNGAN KERJA - Marlius, Doni; Susanti, Febsri; Fernos, Jhon; Harmen, Andre Andhyka (Universitas Prof. Dr. Hazairin SH, 2023)
The purpose of this study was to determine the effect of organizational communication and work environment on the performance of the employees of the West Sumatra Province Investment and One Stop Service (DPMPTSP). The population in this study amounted to 60 employees. The sample taken is the entire population, which is 60 employees. The sampling technique in this study is a total sampling technique. Total sampling technique is a sampling technique in which the entire population is sampled. The analysis technique used in this research is validity, reliability, descriptive analysis, classical assumption test, multiple regression analysis, and t test. The results showed that organizational communication had a positive and significant effect on employee performance, while the work environment had a negative and insignificant effect on employee performance.